Pengembangan Lembar Kerja Peserta Didik pada Mata Pelajaran Gambar Teknik Listrik Berbantuan Software AutoCAD - Rechan Endri Pradana; Oriza Candra (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
This study aims to produce valid and practical Student Worksheets at SMK Muhammadiyah 1 Padang. This study uses a research and development method with a 4D model. The subjects of this study were students of class X TITL at SMK Muhammadiyah 1 Padang in the first semester of the 2021/2022 academic year. Based on the research results, obtained media validation with valid category acquisition, and material validation with valid acquisition. The material expert validators and media experts considered that this LKPD was included in the valid category. The practicality test with teacher respondents obtained results in a very practical category and respondents from class X TITL SMK Muhammadiyah 1 Padang stated that the LKPD learning Electrical Engineering Drawing was categorized as very practical. So it can be concluded that the LKPD for learning Electrical Engineering Drawings is valid and can practically be used in the teaching and learning process in schools.